OVERVIEW OF STUDENT SPECIALIZATION FACULTY OF MEDICINE, UDAYANA UNIVERSITY CLASS OF 2020-2021 - Dewi, Ni Wayan Jemma Tristiana; Putra Manuaba, Ida Bagus Amertha; Sundariyati, I Gusti Ayu Harry; Darmayani, I Gusti Ayu Sri (E-Jurnal Medika Udayana; Vol 13 No 8 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i08.P15, 2024)
Medical Education is someone who studies a particular field of science or field of medical science in charge of developing, transforming, and disseminating technology in the field of medicine through research, education, and community service based on their expertise and education. The choice of a doctor's career is influenced by many factors that influence each other. The goal of this study is to find out the description of specialization and to discover the factors that influence the selection of specialization areas for students of the Faculty of Medicine, Udayana University, Class of 2020-2021. This study used an observational descriptive method with a cross-sectional approach research design with 85 respondents. Data collection using questionnaires and data analysis using Statistical Product and Service Solution (SPSS). Of the 85 respondents, 95.3% of respondents chose a clinician career and 4.7% of respondents chose a non-clinician career. Most of them chose clinician careers, namely other specialists 48.3%, followed by basic specialists 43.5% and support specialists 3.5%. The career that is most in demand by students of the Medical Education Study Program (PSPD) of the Faculty of Medicine, Udayana University batch 2020-2021 is the career of clinicians, especially as other specialists. There was no significant relationship between parents' socioeconomic status, parental education, region of origin, and final Cumulative Achievement Index (GPA) and students' career interests, but career selection motivation was a related factor. Key words: Clinical career, non-clinical career, specialization.